Natural Environment and Social Relationship in the Development of Attentional Network - Federico, Francesca (Frontiers in Psychology, 2020)
The attention mechanism is related to both voluntary and automatic processes, that may be summarized in three distinct networks: alert, orientation and inhibitory control. These networks can be modulated by different contextual and relational situations. Aim of this review is t explain how a combination of natural and social stimuli can positively affect the attentional processes. It has been proposed that the exposition to natural environment can positively affect direct attention, a common resource supporting both executive functioning and self-regulation processes in cognition. It has been suggested that the decrease of the effort required to voluntary control attention from the bottom upwards may improve a beneficial form of internal reflection supporting creative thinking: this may be related to thought patterns for a simultaneous reduction in the effort required to orient attention between thoughts and impressions. In our view, not only exposition to natural and green environment improves attentional processes but also the involvement in social relationship. The development of the orientation and inhibitory control networks is sensitive to the social nature of the stimuli. For instance, in a task, including socially relevant stimuli. the efficiency of these two attentional networks increases in children, in adults and in elderly subjects. Social attention, starting very early in the life (joint attention) is a very important mechanism for the regulation of social relationships. A key for a better development of cognitive functions such as attentional processes is the promotion of the immersion in the natural environment and the involvement in social relationship.